Teaching language and content to linguistically and culturally diverse students : principles, ideas, and materials - Dong, Yu Ren (Language studies in education., 2004)
This book is intended for high school content teachers, preservice teachers preparing to teach in a subject matter area, college faculty involved in both pre-service and in-service teacher preparation, curriculum developers, and policy makers in teacher education. They will find teaching principles as well as concrete ideas for teaching content subject matter knowledge to diverse students.